ANALISIS BAHASA TERHADAP DUGAAN PENCEMARAN NAMA BAIK DAN FITNAH DALAM KONTEN TIKTOKER @GALIHLOSS29 - Natalia Putri Ratnawati; Andi Husna Adawiyah; Ian Wahyuni (Universitas PGRI Palembang, 2024)
This study aims to conduct a linguistic analysis of alleged defamation and slander in the content produced by a TikToker @galihloss29. This research is a literature or library research that utilizes a descriptive qualitative approach with forensic linguistic theory and speech act theory. The study will identify potential legal violations related to defamation and slander. By using the framework of speech act theory as the analytical foundation, this research will understand the communicative purposes behind the content and its effects on the interlocutors. The findings from the analysis of @galihloss29's video uploads, when analyzed using speech act theory, reveal several types of speech acts used. The research found that the video uploads contain 1) five assertive speech acts; 2) three directive speech acts; 3) three expressive speech acts; 4) three commissive speech acts. Therefore, the results of this research are expected to provide deep insights into the role of language in the digital context and its contribution to understanding and addressing legal cases related to defamation and slander.